Do dizer teórico às transposições didáticas: por um exercício da contrapalavra no ensino de língua escrita no PROJOVEM - Azevedo, Gilmara Freire (2010)
This present work is going to show some results developed in the Master Degree research and the Post Graduation project in Language studies (PPgEL) at UFRN, under the orientation of Professor Maria da Penha Casado Alves. This research has questions showed by the Programa Nacional de Inclusão de Jovens PROJOVEM. Concerned to methodology, the research is based on Applied Linguistics and it is qualitative and documental. The corpus of the research are the Manual de Orientações Gerais and the Guias de Estudo. The documents that were used for the research were Guide for general orientation and the Study Guides.The Manual de Orientações Gerais was chosen because is focused on the teacher and the Guias de Estudo was chosen because are focused on the students. The discussions and analysis were based on Bakhtin (1997; 2003), for his studies about the language in a dialogical point of view, Faraco (2001 and 2008) and Suassuna (2006) for their discussions about the Portuguese Language and Geraldi (1997; 2005 and 2006) and Antunes (2003) for their orientation and discussions about the teaching process of the written language. The analysis made in the Reference Topics point that however the program proposes a kind of rupture with the traditional way of teaching, it could not take this change to the Study Guides (Guias de Estudo). The result is a didactic material that reproduces activities based on a conception of a descriptive and prescriptive teaching. What is concerned about the proposals for the textual production, it is shown that it is given in an artificial way, without any expression and with no link to any communicative context and sometimes, with no relation to the topic it was supposed to be related to